ABOUT THE MOVEMENT OF THE RAW COTTON FLY OVER THE SURFACE OF THE PERFORATED MESH OF THE SS-15A SEPARATOR (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article studies the movement of raw cotton particles on the mesh surface of the cotton separator. The test results of the slider with the recommended content are given.
Keywords: Cotton raw material - scraper, mesh surface, piece, vacuum - valve, scraper shaft, working chamber, air, force, torque, rubber, bushing, friction.